Waste to energy technologies for solid waste management a case study of Uganda - Miito, Gilbert John; Banadda, Noble (CIGR Journal, 2016)
Municipal solid waste management is one of the major environmental problems of developing countries. Investments in solid waste management would not only translate into jobs and income but also a cleaner environment. Over years a number of solid waste management technologies have been carried out in many developing parts of the world. Some were successful in generating lasting impacts on the improvement of solid waste management, however, many technologies failed due to unsustainability. This is partly attributed to differences in waste characteristics between developed countries and the less developed countries and the resource constraints in less developed countries. On the other hand, less developed countries are also known for being energy deprived and thus energy recovery as sustainable waste management technology is advocated for in these countries. This paper seeks to review and assess the energy recovery potential from the various sustainable waste technologies in Uganda. The advantages attached to such technologies will be assessed and evaluated. In a further step, a comparative analysis with traditional energy sources like hydro-electricity power and petroleum products powered generators is also presented and discussed. This study concludes that renewable energy sources present Uganda with a rare opportunity to elevate millions out of energy poverty.
Keywords: solid waste, energy, sustainable, Sub-Saharan Africa, biomass, Uganda